Integration of multi-omics analysis reveals metabolic alterations of B lymphocytes in systemic lupus erythematosus - Iperi, Cristian (Clinical immunology (Orlando, Fla.), 2024)
Copyright © 2024 The Authors. Published by Elsevier Inc. All rights reserved.